Leakage-free solution-processed organic light-emitting diode using a ternary host with single-diode emission area up to 6 × 11.5 cm2. Issue 19 (4th April 2019) - Liao, Si-Yi; Su, Hsiao-Tso; Hsiao, Yung-Hung; Chang, Yu-Fan; Chang, Chiung-Wen; Niu, Mu-Chun; Meng, Hsin-Fei; Yen, Chun; Chao, Yu-Chiang; Chang, Chih-Yu; Zan, Hsiao-Wen; Horng, Sheng-Fu
Abstract : OLEDs with an emission layer consisting of ternary mixed host materials are prepared with operation of over 1600 hours. Abstract : The electrical current leakage and stability are studied for solution-processed OLEDs with areas of 4.45 mm 2, 3 × 3.2 cm 2, and 6 × 11.5 cm 2 . The emission layer of the OLED has a ternary or binary mixed host with hole-transporting molecules tris(4-carbazoyl-9-ylphenyl)amine (TCTA) and 9-(4- tert -butylphenyl)-3, 6-bis(triphenylsilyl)-9 H -carbazole (CzSi), together with the electron-transporting molecule 2, 7-bis(diphenylphosphoryl)-9, 9′-spirobi[fluorene] (SPPO13). The phosphorescent emitters are Ir(mppy)3 for green and bis[4-(4- tert -butylphenyl)thieno[3, 2- c ]pyridine][ N, N ′-diisopropylbenamidinato]iridium(iii ) (PR-02) for orange. Poly[(9, 9-dioctylfluorenyl-2, 7-diyl)- co -(4, 4′-( N -(4- sec -butylphenyl))diphenylamine)] (TFB) is used as the hole transport layer and PEDOT:PSS is used as the hole injection layer. On top of the emission layer, CsF/Al is deposited by thermal evaporation as the cathode. All organic layers are deposited by blade coating and the initial current leaking defects can be avoided by careful control of the coating conditions. The detrimental burning point caused by a local current short developed after long-time operation can be avoided by reducing the operation voltage using a ternary mixed host. The operation voltage is only 4 V at 100 cd m −2 and 5 V at 250 cd m −2 for the green emitting device. Furthermore, the crystallization defect is reduced by the ternary host. For the orange emitting device, the binary host is good enough with an operating voltage of 5 V at 100 cd m −2 . For an area as large as 6 × 11.5 cm 2, the OLED shows good stability and there is no burning point after an operation of over 1600 hours.